New diagnostic tools (Hematology Meeting Reports, 2009)
Medical microbiology is a clinical discipline that evolves slowly and the majority of diagnoses relies still upon demonstrable growth of an infectious microorganism. However, various new diagnostic technologies have been introduced into laboratory practice over the past few decades.1 As recently stated by Isenberg,2 molecular biology has the potential to revolutionize the diagnosis of infectious disease in order to optimize the care of infected patients, whether they are in hospital or in the community. Molecular tests promise to be extremely useful also in therapy, epidemiological investigations, and infection control.